Can Understanding How Middle Managers Make Decisions Help Design Effective Results-Based Financing Mechanisms in Education? - World Bank (World Bank, Washington, DC, 2020)
The Results in Education for All Children (REACH) Trust Fund supports and disseminates research on the impact of results-based financing on learning outcomes. The Evidence series highlights REACH grants around the world to provide empirical evidence and operational lessons helpful in the design and implementation of successful performance-based programs.